2008
DOI: 10.1007/s00210-008-0308-5
|View full text |Cite
|
Sign up to set email alerts
|

Subnanomolar dopamine D3 receptor antagonism coupled to moderate D2 affinity results in favourable antipsychotic-like activity in rodent models: I. neurochemical characterisation of RG-15

Abstract: RG-15 (trans-N-[4-[2-[4-(3-cyano-5-trifluoromethyl-phenyl)-piperazine-1-yl]-ethyl]-cyclohexyl]-3-pyridinesulfonic amide dihydrochloride) displayed subnanomolar affinity to human and rat dopamine D3 receptors (pKi 10.49 and 9.42, respectively) and nanomolar affinity to human and rat D2 receptors (pKi 8.23 and 7.62, respectively). No apparent interactions were found with the other 44 receptors and four channel sites tested in this study. RG-15 inhibited dopamine-stimulated [35S]GTPgammaS binding in membranes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Previous investigations indicated that D 2 antagonism was required for antipsychotic efficacy, but that D 3 receptor antagonism might impart beneficial effects on cognition, while attenuating the EPS. It was hypothesized that the conjunction of subnanomolar D 3 receptor antagonism together with nanomolar D 2 receptor antagonism should therefore yield an antipsychotic compound with a superior side effect profile [28,29].…”
Section: Chemistrymentioning
confidence: 99%
“…Previous investigations indicated that D 2 antagonism was required for antipsychotic efficacy, but that D 3 receptor antagonism might impart beneficial effects on cognition, while attenuating the EPS. It was hypothesized that the conjunction of subnanomolar D 3 receptor antagonism together with nanomolar D 2 receptor antagonism should therefore yield an antipsychotic compound with a superior side effect profile [28,29].…”
Section: Chemistrymentioning
confidence: 99%
“…Dopamine, 3,4-dihydroxyphenyl acetic acid (DOPAC), homovanillic acid (HVA), serotonin (5-HT), and 5-hydroxyindolyl acetic acid (5-HIAA) were determined by high-pressure liquid chromatography coupled with electrochemical detection as described (Kiss et al, 2008) and expressed in pmol/g tissue. Ratios of (DOPACϩHVA)/DA and 5-HIAA/5-HT, respectively, were calculated as an index of DA and 5-HT turnover, respectively.…”
Section: Determination Of Dopamine Serotonin and Metabolites In Moumentioning
confidence: 99%
“…In these experiments, drug-or vehicle-treated animals received NSD-1015 intraperitoneally 30 min before decapitation. DOPA levels were determined from dissected brain regions by highpressure liquid chromatography coupled with electrochemical detection (Kiss et al, 2008).…”
Section: Determination Of Dopa Accumulationmentioning
confidence: 99%
See 2 more Smart Citations